UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI BERBEDA ITU INDAH DI KELAS III SEKOLAH MIS AL-BASHIRAH - Indah Permadani; Dinda Yarshal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the learning motivation of third-grade students at MIS Al-Bashirah in the Pancasila Education subject, specifically on the topic "Differences Are Beautiful," through the use of interactive learning media. The background of this research is the low level of student motivation, which affects their participation and interest in conventional learning processes. This study employs Classroom Action Research (CAR) with two cycles. The research subjects were 22 third-grade students at MIS Al-Bashirah. Data were collected through observation, interviews, and documentation. The collected data were analyzed using qualitative descriptive methods. The results of the study showed that the use of interactive learning media successfully increased students' learning motivation. This was evidenced by the increase in motivation indicators from 30% in the pre-cycle, 62% in the first cycle, and 86% in the second cycle. Qualitatively, observations indicated improvements such as greater student comfort during learning, active participation, clear interest in the material, and improved classroom order during lessons. These improvements demonstrate that interactive learning media are effective in creating a more engaging learning environment and encouraging student motivation. It is concluded that interactive learning media can be an effective solution to enhance students’ learning motivation in Pancasila Education. It is recommended that teachers integrate interactive learning media into their teaching practices to create more innovative and meaningful learning experiences.